Degradation of Polycarbonate by a Polyester-Degrading Strain, Amycolatopsis sp. Strain HT-6 - Pranamuda, Hardaning (American Society for Microbiology, 1999)
Amycolatopsis sp. strain HT-6, a poly(tetramethylene succinate) (PTMS)-degrading actinomycete, was observed to degrade poly(tetramethylene carbonate) (PTMC). In a liquid culture with 150 mg of PTMC film, 59% degradation was achieved, but with a low yield of cell growth. On the other hand, PTMS copolymerized with a small amount of PTMC, forming a copolyester carbonate (PEC) that was completely and rapidly degraded with a high yield of cell growth.